2017
DOI: 10.1007/s00429-017-1392-4
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic regulation through GABA and acetylcholine muscarinic receptors of motor trigeminal neurons following sleep deprivation

Abstract: Muscle tone is regulated across sleep-wake states, being maximal in waking, reduced in slow wave sleep (SWS) and absent in paradoxical or REM sleep (PS or REMS). Such changes in tone have been recorded in the masseter muscles and shown to correspond to changes in activity and polarization of the trigeminal motor 5 (Mo5) neurons. The muscle hypotonia and atonia during sleep depend in part on GABA acting upon both GABAA and GABAB receptors (Rs) and acetylcholine (ACh) acting upon muscarinic 2 (AChM2) Rs. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…Following SD, the proportion and luminance of the AChM2Rs on the plasma membrane of the RFMes GAD+ neurons increased relative to SC, presumably due to prolonged activity of RFMes GABAergic neurons during enforced waking. The proportion and density of the AChM2Rs on GAD+ neurons returned to control level with SR, presumably due to less activity or inactivity of the GABAergic neurons following SR. Our results here are parallel to the increase in proportion and density of AChM2Rs seen on the membrane of the Mo5 neurons following SD with prolonged waking, when these neurons are also presumed to be active ( Toossi et al, 2017 ).…”
Section: Discussionsupporting
confidence: 78%
“…Following SD, the proportion and luminance of the AChM2Rs on the plasma membrane of the RFMes GAD+ neurons increased relative to SC, presumably due to prolonged activity of RFMes GABAergic neurons during enforced waking. The proportion and density of the AChM2Rs on GAD+ neurons returned to control level with SR, presumably due to less activity or inactivity of the GABAergic neurons following SR. Our results here are parallel to the increase in proportion and density of AChM2Rs seen on the membrane of the Mo5 neurons following SD with prolonged waking, when these neurons are also presumed to be active ( Toossi et al, 2017 ).…”
Section: Discussionsupporting
confidence: 78%
“…These results indicated that homeostatic bidirectional changes in GABA A Rs occur in arousal and sleep circuits as a function of their state selective activities. This same principle was found to apply to other wake-active cell groups, including BF ACh neurons [178], motor neurons [179], and excitatory cortical neurons [180].…”
Section: Homeostatic Regulation Of Arousal and Sleep Circuitsmentioning
confidence: 62%
“…Can activity‐dependent processes interact with aspects of the organismal environment to constrain their expression? An appropriate amount of compensation during chronic inactivity is an interesting counterexample to rodents and humans because a loss of activity input to motoneurons may lead to overcompensation (D'Amico, Condliffe, Martins, Bennett, & Gorassini, ; Toossi, Cid‐Pellitero, & Jones, ) or under compensation (Alvarez, Bullinger, Titus, Nardelli, & Cope, ; Cormery, Beaumont, Csukly, & Gardiner, ; Rotterman, Nardelli, Cope, & Alvarez, ) that causes motor impairment. Perhaps hibernating animals may hold insights into the mechanisms by which compensatory plasticity can be regulated across time to stabilize motor performance after prolonged and variable bouts of inactivity.…”
Section: Open Questions and The Use Of Hibernating Animals As Models mentioning
confidence: 99%